2016
DOI: 10.11113/jt.v78.8822
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Biomarker From Brown Coal, Sangatta Coalfield, East Borneo of Middle Miocene to Late Miocene Age

Abstract: A section of the Sangatta coalfield in the Balikpapan formation located in Kutai Basin, East Borneo, Indonesia, is the Inul area, located North of Pinang Dome. This section of the coalmine has coals with low calories (ca. 4379 cal/g), which is why they cannot be used optimally yet. The reasons of using low calorie coals are besides from being used as a mixing ingredient for the blending process of high calorie coals, they are also used to diversify the coals through the process of coal liquefaction (coal to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The Miocene period was dominated by Angiosperm plants and few conifers [12,13,14]. This is proven by several previous studies which found aromatic hydrocarbons such as retene, tetrahydroretene, simonellite, and some tricyclic diterpenoids in oil and coal as coniferous organic material indication [13,15]. Naphthalene derivatives and sesquiterpenoid group such as cadalene were also found abundantly in some Miocene period oil and condensate samples.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…The Miocene period was dominated by Angiosperm plants and few conifers [12,13,14]. This is proven by several previous studies which found aromatic hydrocarbons such as retene, tetrahydroretene, simonellite, and some tricyclic diterpenoids in oil and coal as coniferous organic material indication [13,15]. Naphthalene derivatives and sesquiterpenoid group such as cadalene were also found abundantly in some Miocene period oil and condensate samples.…”
Section: Introductionmentioning
confidence: 76%
“…The other naphthalene derivatives was identified as ionene based on m/z 159 fragmentogram [15,36,40]. The existence of this compound is not specific, because it could be formed through carotenoid [41] and labdane degradation which are the main components of conifers resin in the oxidative environment [42,43].…”
Section: Naphthalene Derivativesmentioning
confidence: 99%
See 2 more Smart Citations